HIGH-RESOLUTION RECORD OF URANIUM ISOTOPIC COMPOSITION OF PALEO-BAIKAL WATER DURING THE LAST 100 KA - Zhuchenko N.A.; Chebykin E.P.; Goldberg E.L.; Stepanova O.G. (My University, 2007)
The study of bottom sediments of Lake Baikal attracts great interest as a tool for reconstruction of the paleoclimate in continental Asia. Several climate-sensitive indicators of variable paleoproductivity and vegetation of the lake, as well as provenances of the terrigenous material, have been found to date. Uranium isotopes occupy a special position in this respect, because their contents in sediments of Lake Baikal correlate with the volume of river inflow. This correlation made it possible to reconstruct variations in climate humidity in East Siberia to reconstruct. Since a substantial excess of 234U relative to 238U was revealed in the present-day water and surficial sediments of Lake Baikal, Edgington proposed a geochemical model of supply and precipitation of uranium in sediments of this lake in order to carry out their direct dating.